Cedratvirus lausannensis – digging into Pithoviridae diversity. (14th August 2017) - Bertelli, Claire; Mueller, Linda; Thomas, Vincent; Pillonel, Trestan; Jacquier, Nicolas; Greub, Gilbert
Summary: Amoeba‐infecting viruses have raised scientists' interest due to their novel particle morphologies, their large genome size and their genomic content challenging previously established dogma. We report here the discovery and the characterization of Cedratvirus lausannensis, a novel member of the Megavirales, with a 0.75–1 µm long amphora‐shaped particle closed by two striped plugs. Among numerous host cell types tested, the virus replicates only in Acanthamoeba castellanii leading to host cell lysis within 24 h. C. lausannensis was resistant to ethanol, hydrogen peroxide and heating treatments. Like 30 000‐year‐old Pithovirus sibericum, C. lausannensis enters by phagocytosis, releases its genetic content by fusion of the internal membrane with the inclusion membrane and replicates in intracytoplasmic viral factories. The genome encodes 643 proteins that confirmed the grouping of C. lausannensis with Cedratvirus A11 as phylogenetically distant members of the family Pithoviridae . The 575, 161 bp AT‐rich genome is essentially devoid of the numerous repeats harbored by Pithovirus, suggesting that these non‐coding repetitions might be due to a selfish element rather than particular characteristics of the Pithoviridae family. The discovery of C. lausannensis confirms the contemporary worldwide distribution of Pithoviridae members and the characterization of its genome paves the way to better understand their evolution.